THE INFLUENCE OF ONLINE CAMBRIDGE DICTIONARY TOWARD STUDENTS’ PRONUNCIATION AND VOCABULARY MASTERY - Rosita Ambarwati; Berlinda Mandasari (fsip.teknokrat.ac.id, 2020)
Dictionary has become one important tool for learning a foreign language. Many kinds of dictionaries can be used for students who want to learn a foreign language. An online dictionary is one of the technologies that can be used for learning a foreign language. Nowadays in the digital era, students can use it through internet networking. Thus, this study discusses the influence of the online Cambridge dictionary on students' pronunciation and vocabulary of students at Universitas Teknokrat Indonesia (UTI). Subjects of the research were 25 students who take Academic Writing subject majoring in English Education study program. Data were then analyzed by using descriptive analysis. Data were collected through questionnaires and interviews, the student was given a questionnaire and interview related to an alternative reference in technology for learning vocabulary and pronunciation especially online Cambridge dictionary. As a result of this study, the online Cambridge dictionary influences student pronunciation and vocabulary in terms of pronunciation mastery and vocabulary enrichment. It is suggested that the online Cambridge dictionary can be an alternative solution to solve the problem of pronunciation and vocabulary mastery.